Normal Faulting Along the Kythira-Antikythira Strait, Southwest Hellenic Forearc, Greece - Veliz-Borel, Violeta; Mouslopoulou, Vasiliki; Nicol, Andrew; Begg, John; Oncken, Onno (Frontiers in Earth Science, 2022)
Upper-plate normal faults along forearcs often accumulate slip during >Mw 6 earthquakes. Such normal faults traverse the forearc of the Hellenic Subduction System (HSS) in Greece and are the focus of this study. Here, we use detailed field-mapping and analysis of high-resolution Digital Elevation Models (DEMs) to study 42 active normal faults on the islands of Kythira and Antikythira in the Aegean Sea. Onshore fault kinematic data are complemented by seabed bathymetry mapping of ten offshore faults that extend along the Kythira-Antikythira Strait (KAS). We find that normal faults in the KAS have lengths of ∼1–58 km and scarps ranging in height from 1.5 m to 2.8 km, accommodating, during the Quaternary, trench-orthogonal (NE-SW) extension of ∼2.46 ± 1.53 mm/a. Twenty-eight of these faults have ruptured since the Last Glacial Maximum, with their postglacial (16 ± 2 ka) displacement rates (0.19–1.25 mm/a) exceeding their Quaternary (≤0.7–3 Ma) rates (0.03–0.37 mm/a) by more than one order of magnitude. Rate variability, which is more pronounced on short (<8 km) faults, is thought to arise due to temporally clustered paleoearthquakes on individual KAS faults. When displacement accumulation is considered across the entire onshore fault network, rate variability between the two time-intervals examined decreases significantly (2.79 ± 0.41 vs 1.29 ± 0.99 mm/a), a feature that suggests that earthquake clustering in the KAS may occur over ≤16 ka timescales.